Do Rare Events Explain CDX Tranche Spreads? - SEO, SANG BYUNG; WACHTER, JESSICA A. (Journal of Finance, 2018)
ABSTRACT We investigate whether a model with time‐varying probability of economic disaster can explain prices of collateralized debt obligations. We focus on senior tranches of the CDX, an index of credit default swaps on investment grade firms. These assets do not incur losses until a large fraction of previously stable firms default, and thus are deep out‐of‐the money put options on the overall economy. When calibrated to consumption data and to the equity premium, the model explains the spreads on CDX tranches prior to and during the 2008 to 2009 crisis.